Molecular characterization and detection of African oil palm ringspot virus - Lozano Potes, Iván; Morales, Francisco José; Martínez, A.K.; Pena, E. (Wiley, 2010)
African oil palm ringspot virus (AOPRV) had been previously described as a fovea-like virus associated with a lethal disease of African oil palm (Elaeis guineensis) in South America. The original report was based on partial sequence and a distant relationship between AOPRV and Apple stem pitting virus, Apricot latent virus and Grapevine rupestris stem pitting-associated virus, definitive species of the genus Foveavirus, family Flexiviridae. We report the full sequence of the RNA genome of AOPRV, and demonstrate that this virus is more closely related to two unassigned virus species of the family Flexiviridae (Cherry green ring mottle virus and Cherry necrotic rusty mottle virus) than to any definitive species of the genus Foveavirus. Thus, AOPRV should be considered as a new species of the Flexiviridae until the International Committee on Taxonomy of Viruses (ICTV) resolves the taxonomic status of the increasing number of unassigned species in this family. The molecular characterization of AOPRV has provided a highly sensitive and reliable RT-PCR assay for the early detection of AOPRV in different genotypes of African, American (E. oleifera) and hybrid oil palms.